Bridging The Gap Between Data-Driven Decision Making and Human-Centric Management in Organisations - Alade, Olanrewaju; Ogunbadejo, Mobolaji; Ayilara-Adewale, Oluwatobi Adedamola; Sokunbi, Ayodeji Julius (International Journal of Scientific Research and Management (IJSRM), 2025)
The integration of data-driven decision-making (DDDM) and human-centric management has emerged as a transformative strategy for modern organizations seeking to thrive in an increasingly dynamic and competitive landscape. This paper explores the synergy between these two approaches, highlighting their theoretical foundations, advantages, challenges, and practical applications. It examines how DDDM leverages advanced tools and analytics to enhance efficiency and scalability while addressing the critical role of human-centric management in fostering employee engagement, creativity, and organizational resilience. The study identifies key barriers to integration, including technical challenges such as data silos and legacy systems, cultural resistance to change, and ethical considerations around data use and privacy. Strategies for overcoming these obstacles are proposed, emphasizing cross-functional collaboration, alignment with organizational values, and the design of adaptive systems that prioritize human interaction. Drawing on case studies and best practices, this paper also explores how organizations can successfully balance technological innovation with human-centric approaches, particularly during digital transformation initiatives. Future research opportunities are outlined, including the exploration of emerging technologies, ethical frameworks, and cross-cultural adaptations, to further advance the integration of these paradigms. By bridging the gap between DDDM and human-centric management, this study provides a comprehensive framework for achieving sustainable organizational success that values both technological innovation and the human element at its core.